Synthesis, Characterization and Antibacterial Activity of New Derivatives of Imidazolidine having Sulfamethoxazole Moiety - Enas k. Abd alazez; Ayad M.R. Raauf; karima F. Ali (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2019)
This work includes Synthesis of new series of sulfa drugs derived from sulfamethoxazole containing substituted Imidazolidine moiety.  These compounds expected to have antibacterial activity, due to their Imidazolidine moiety This work includes synthesis of some new